2022
DOI: 10.1111/1365-2664.14198
|View full text |Cite|
|
Sign up to set email alerts
|

Achieving international biodiversity targets: Learning from local norms, values and actions regarding migratory waterfowl management in Kazakhstan

Abstract: 1. Migratory species are protected under international legislation; their seasonal movements across international borders may therefore present opportunities for understanding how global conservation policies translate to local-level actions across different socio-ecological contexts. Moreover, local-level management of migratory species can reveal how culture and governance affects progress towards achieving global targets. Here, we investigate potential misalignment in the two-way relationship between global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…When animals that live in mountains move north, they are able to locate environments that are ideal for them. Loss of topography and range, however, may imprison migratory species in restricted and unsuitable habitats (Jones et al, 2022). For instance, one study found that the American pika has been wiped out or severely reduced in some areas, with climate change being the primary cause of its demise (Palita, 2016).…”
Section: Climate Change Effects On Biodiversitymentioning
confidence: 99%
“…When animals that live in mountains move north, they are able to locate environments that are ideal for them. Loss of topography and range, however, may imprison migratory species in restricted and unsuitable habitats (Jones et al, 2022). For instance, one study found that the American pika has been wiped out or severely reduced in some areas, with climate change being the primary cause of its demise (Palita, 2016).…”
Section: Climate Change Effects On Biodiversitymentioning
confidence: 99%
“…Northern Kazakhstan can be singled out, there is a powerful Central Asian migration route. Every year millions of birds visit this territory during spring and autumn migrations (Yerokhov, 2013;Cresswell et al, 1999;Zuban et al, 2020;Jones et al, 2022;Kamp et al, 2015). At the same time, the development of ornithological tourism in the northern regions of Kazakhstan is hindered by the weak study of promising territories for the organization of ornithological tourism.…”
Section: Introductionmentioning
confidence: 99%